A Strong Decrease in TIMP3 Expression Mediated by the Presence of miR-17 and 20a Enables Extracellular Matrix Remodeling in the NSCLC Lesion Surroundings - Czarnecka, Karolina H.; Szmyd, Bartosz; Barańska, Magda; Kaszkowiak, Marcin; Kordiak, Jacek; Antczak, Adam; Pastuszak-Lewandoska, Dorota; Brzeziańska-Lasota, Ewa (Frontiers in Oncology, 2019)
Lung cancer is one of the most common causes of death worldwide with a relatively high fatality rate and a mean 5-year survival of about 18%. One of the hallmarks of cancer is the extracellular matrix (ECM) remodelling, which is crucial for metastasis. This process may be regulated by miRs targeting metalloproteinases (MMPs) associated with the ECM breakdown and metastatic process or blocking the action of tissue inhibitors of metalloproteinases (TIMPs). Search for early biomarkers is essential in detecting non-small cell lung cancer (NSCLC) and distinguishing its subtypes: Adenocarcinoma (AC) from Squamous Cell Carcinoma (SCC), enabling targeted chemotherapy. MiR-17 and miR-20a targeting MMP2 and TIMP3 were selected by TCGA data analysis with further validation using miRTarBase and literature. The study group comprised 47 patients with NSCLC (AC and SCC subtypes). RNA was isolated from the tumour and normal-looking neighbouring tissue (NLNT) free of cancer cells. MiRs from peripheral blood exosomes were extracted on admission and 5-7 days after surgery. Gene and miRs expression were assessed in qPCR using TaqMan probes. The MMP2 has been expressed on a similar level in NLNT, as in cancer. While, TIMP3 expression was decreased both in cancer tissue and NLNT, with significantly lower expression in cancer. TIMP3 downregulation in NLNT and in SCC subtype correlated negatively with miR-20a. The preoperative miR-17 expression was significantly higher among patients with SCC compared to AC. Receiver operating characteristic (ROC) analysis of miR-17 as AC subtype classifier revealed 90% specificity and 48% sensitivity in optimal cut-off point with area under ROC curve (AUC): 0.71 (95%CI:0.55–0.87). Within NSCLC subtypes: a strong negative correlation between pack-years (PY) and TIMP3 expression was observed for NLNT in the SCC group. The TIMP3 silencing observed in the NLNT and its negative correlation with presurgical expression of miR-20a (from serum exosomes), suggest that miRs can influence ECM remodelling at a distance from the centre of the lesion. The miRs expression pattern in serum obtained before surgery significantly differs between AC and SCC subtypes. Moreover, decreased TIMP3 expression in NLNT (in SCC group) negatively correlates with the amount of tobacco smoked in a lifetime in PY.